Experience-driven leader development : models, tools, best practices, and advice for on-the-job development - McCauley, Cynthia D. (Cynthia Denise), 1958-; DeRue, D. Scott; Yost, Paul R.; Taylor, Sylvester (Hoboken : Wiley, 2013)
This book is written for human resource, organization development, and training professionals who need real-world best practices that show who actual workplace learning approaches work and how they can be applied. Co-published with the acclaimed Center for Creative Leadership, this important book offers a compendium of best practices, tools, techniques, processes, and other resource resources to harness the developmental power of work experiences for leadership development. In addition the book includes illustrative case studies of leadership approached that have worked in such forward thinkin.
Part III. Human resource systems : designed for experience-driven development -- ch. 47. Integrated talent management and experience-based development / Norm Tonina -- Section H. Selection and on-boarding -- ch. 48. Identifying and assessing for learning abiliity / Paul Yost and Jillian McLellan -- ch. 49. On-the-job development that starts on day one / Drad Borland -- ch. 50. New leader assimilation / Tanya Boyd -- ch. 51. Virtual on-boarding / Ritesh Daryani -- Section I. Managers as developers -- ch. 52. Leaders coaching leaders : cascading leadership development through the organization / Robert J. Thomas, Claudy Jules, and Joshua Bellin -- ch. 53. An exercise for manager : developing talent through assignments / Cynthia McCauley -- ch. 54. Performance and development through conversation / Jonathan Winter -- Section J. Performance management -- ch. 55. Performance management and leadership development : paradox or potential? / Robert McKenna and Robleh Kirce -- ch 56. Performance management catalysts for experience-driven development / Paul Yost -- Section K. Training, development, and beyond -- ch . 57. Training and experience-driven development / Paul Yost -- ch. 58. Bringing the real work into the classroom / Elaine Biech -- ch. 59. Cultivating learning agility : lessons from the microfinance sector / Lyndon Rego, Vandana Viswanathan, and Peg Ross -- ch. 60. HoTspots (HubsoTraining) : a blended group learning solution to extend traditional training / Eric Berg -- ch. 61. Building experience into simulations / James Chisholm, Greg Warman, and Andrew Webster -- ch. 62. Mentoring : building leaders in powerful developmental relationships / Dana Kendall -- Section L. Action Learning -- ch. 63. Business driven action learning / Yury Boshyk -- ch. 64. Action learning with community-based nonprofits / Lynn Fick-Cooper and Shera Clark -- ch. 65. Better together : building learning communities across organizations / Jan Wilmott -- ch. 66. Communities of practice : building and sustaining global learning communities / Yury Boshyk -- Section M. Succession management -- ch. 67. Succession planning : developing general managers through experience / Mary M. Plunkett -- ch. 68. Building breadth and depth through experience / Jennifer Kennedy Marchi -- ch. 69. Profiles for success : building a framework for internal transitions / Tanya Boyd -- ch. 70. Hot jobs, hot people : sharing leadership talent across organizations / Jeffrey J. McHenry -- ch. 71. Multicultural women in the pipeline : finding hidden treasure / Ella L.J. Edmondson Bell -- Part IV. The organization : enabler of experience-driven development -- Section N. Frameworks for assessing organizations -- ch. 72. Organizational climate for development / Cynthia McCauley -- ch. 73. Creating the "and" organization : seeing leadership development as a key strategic issue / Stephen R. Mercer -- Section O. Desinging tools for widespread use -- ch. 74. Leading from where you are / Paul Yost and Emily Pelosi -- ch. 75. My needs, their needs : designing high-value development tools / Rob McKenna, Mary M. Plunkett, and Kayode Adeuja -- ch. 76. Built to last : sustainable on-the-job development interventions for the entire organization / Paul Yost and Emily Pelosi -- Section P. Influencing organizational leaders -- ch. 77. Building support for experience-based development / Brad Borland -- ch. 78. The power of stories in leadership development / Paul Yost and JIllian McLellan -- ch. 79. Assessing learning's impact on careers / Richard A. Guzzo and Haif R. Nalbantian -- ch. 80. Teaching senior leaders the dynamics of derailment / Cynthia McCauley and Sylvester Taylor -- Section Q. Solutions to specific obstacles -- ch. 81. Strengthening executive mobility / Nora Gardner and Cameron Kennedy -- ch. 82. Talent ecosystes : building talent through strategic partnerships / D. Scott DeRue.
Includes bibliographical references and index.
Opportunities to Learn.
Print version record.
John Wiley and Sons
Keywords: Leadership; Executive ability; Leadership; Aptitude pour la direction; Executive ability; Leadership